Sex and breeding behaviour of the Sicilian snail-shell bee (Rhodanthidium siculum Spinola, 1838; Apoidea-Megachilidae): preliminary results - Erbar, Claudia; Leins, Peter (Arthropod-plant interactions, 2017)
In spring 2014 and 2016, we studied Rhodanthidium siculum in dunes south of Syracuse (Sicily). The females search for one of the frequently empty snail shells (mostly of Theba pisana), checking their size. In a suitable snail shell, a mixture of sand and saliva is deposited in the navel. A severe struggle among several males gets started. At every opportunity, the males try to copulate with the females. Large males occupy the snail shell that is used by the female to bring in pollen and nectar (preferably from Galactites tomentosus, Centaurea sphaerocephala, Glebionis coronaria and Lotus creticus). The procedure of harvesting lasts about 2-3 h, sometimes several hours. During this period, the female is visited for copulation every 2 min (initially even more frequently), preferentially by one large male, but small males occasionally mate as well. After laying one or two eggs, the female closes the snail shell with pieces of seashells or snail shells, aggregated with sand and saliva. The female transports the closed snail shell to a safe site. Depending on weather conditions, this may take several days. The maximum distance of movement observed was about 10 m. Finally, the completed snail shell will be buried, most often beneath a plant. The burial follows a certain pattern of movement. Females ensure higher pollination efficiency than the males due to their higher flower constancy.